2004
DOI: 10.1017/s1357729800090251
|View full text |Cite
|
Sign up to set email alerts
|

Growth and carcass composition of lambs of two breeds and their cross grazing ryegrass and clover swards

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The same authors reported significant differences for HCY and CCY. Likewise, other authors have reported differences among sheep breeds with distinct aptitudes for HCW and CCW (Macfarlane et al, 2004;Kashan et al, 2005;Ekiz et al, 2009). In the case of HCY and CCY, studies have found differences among breeds (Kremer et al, 2004;Rodrigues et al, 2006;Ekiz et al, 2009).…”
Section: Breed Effectmentioning
confidence: 75%
“…The same authors reported significant differences for HCY and CCY. Likewise, other authors have reported differences among sheep breeds with distinct aptitudes for HCW and CCW (Macfarlane et al, 2004;Kashan et al, 2005;Ekiz et al, 2009). In the case of HCY and CCY, studies have found differences among breeds (Kremer et al, 2004;Rodrigues et al, 2006;Ekiz et al, 2009).…”
Section: Breed Effectmentioning
confidence: 75%
“…It has been found that superior genotypes can express their superiority only to an extent that is set by the quality of the environment ; Macfarlane et al, 2004). The genetic difference in growth rate was found to decrease steadily as the environment worsened, both between selection lines and between breeds (Macfarlane et al, 2004). Similarly, differences in husbandry between purebred and commercial farms may play a role.…”
Section: Sire Index and Breed Influencesmentioning
confidence: 93%
“…Although the breeds and crossbreeds used in the study by Speijers et al (2009) were perhaps more associated with hill farming environments, the results demonstrated clear differences between three different diets and between the different breeds used. Macfarlane et al (2004) observed significant differences in the growth responses of lambs grazing different sward types, which, along with the results of Speijers et al (2009), demonstrate that differences in the magnitude of genetic superiority can exist between animals on different grazing types.…”
Section: Discussionmentioning
confidence: 54%
“…The increased level of detail gained in the present study was predominantly related to grazing management throughout the season, as well as the provision of supplementary feeding, vitamins and minerals. Studies by both Macfarlane et al (2004) and Speijers et al (2009) demonstrated significant results when breed by feed type interactions were examined. Although the breeds and crossbreeds used in the study by Speijers et al (2009) were perhaps more associated with hill farming environments, the results demonstrated clear differences between three different diets and between the different breeds used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation